mTORC2/Akt activation in adipocytes is required for adipose tissue inflammation in tuberculosis - Martinez, Nuria (2019)
Background: Mycobacterium tuberculosis has co-evolved with the human host, adapting to exploit the immune system for persistence and transmission. While immunity to tuberculosis (TB) has been intensively studied in the lung and lymphoid system, little is known about the participation of adipose tissues and non-immune cells in the host-pathogen interaction during this systemic disease. Methods: C57BL/6J mice were aerosol infected with M. tuberculosis Erdman and presence of the bacteria and the fitness of the white and brown adipose tissues, liver and skeletal muscle were studied compared to uninfected mice. Findings: M. tuberculosis infection in mice stimulated immune cell infiltration in visceral, and brown adipose tissue. Despite the absence of detectable bacterial dissemination to fat tissues, adipocytes produced localized pro-inflammatory signals that disrupted adipocyte lipid metabolism, resulting in adipocyte hypertrophy. Paradoxically, this resulted in increased insulin sensitivity and systemic glucose tolerance. Adipose tissue inflammation and enhanced glucose tolerance also developed in obese mice after aerosol M. tuberculosis infection. We found that infection induced adipose tissue Akt signaling, while inhibition of the Akt activator mTORC2 in adipocytes reversed TB-associated adipose tissue inflammation and cell hypertrophy. Interpretation:Our study reveals a systemic response to aerosol M. tuberculosis infection that regulates adipose tissue lipid homeostasis through mTORC2/Akt signaling in adipocytes. Adipose tissue inflammation in TB is not simply a passive infiltration with leukocytes but requires the mechanistic participation of adipocyte signals.